Assessing the risk of low energy availability, bone mineral density and psychological strain in endurance athletes - Charlotte R. Gowers; Christopher J. McManus; Henry C. Chung; Ben Jones; Jamie Tallent; Sally P. Waterworth (Journal of the International Society of Sports Nutrition)
Background Adequate energy intake is crucial for athletic performance and recovery. However, many endurance athletes experience Low Energy Availability (LEA), which, if prolonged, can detrimentally impact both health and performance.Methods A total of 55 endurance athletes (23 females; 45  ±  13 years, 1.64  ±  0.06 m, 64.4  ±  11.4 kg and 32 males; 44  ±  13 years, 1.76  ±  0.18 m, 78.8  ±  9.2 kg) underwent physical assessments and completed questionnaires on dietary habits, training loads, and psychological stress. Dual-Energy X-ray Absorptiometry (DEXA) scans measured bone mineral density (BMD) in the lumbar L1-L4 spine, and body composition. Risk of LEA burnout, and psychological strain were assessed using sport-specific questionnaires.Results Seventy-seven percent of female athletes were identified as at risk of LEA by the LEAF-Q. These females had higher body weight and fat percentage than those at low risk of LEA. Male athletes had a higher prevalence of low lumbar BMD (31%) compared to females, associated with older age, and longer training histories. Although only 9% of female athletes had low-BMD, those affected had a history of amenorrhea and were identified as at risk of LEA by the LEAF-Q.Conclusion A high proportion of endurance athletes had low-BMD and were at risk of LEA. This underscores the need for targeted nutritional strategies to mitigate the risks associated with LEA and promote overall athlete well-being.